Java for dummies - Burd, Barry (For dummies, 2022)
Learn to write practical, reusable code with the straightforward tutorials and tips in the newest edition of this For Dummies bestseller  Do you speak Java? No, we're not talking about your morning cup 'o joe. We mean the world's most popular programming language that runs on almost any computer!  If you're looking to get started-or up your game-with Java, then Java For Dummies is the guide you need. In this book, you'll:  Take control of your program flow  Program with classes, objects, and methods Use Java's functional programming features Explore Java 17, the latest long-term support release  This up-to-date handbook covers the latest developments in Java, including the new 'switch' statement syntax. So, if you're ready to dive into one of the most practical (and coolest!) programming languages around, it's time you picked up Java For Dummies.